Relationship of servant leadership, ethical leadership and work engagement: The role of proactive personality as moderator - Fazly, Noordin (2019)
The purpose of this study is to examine the relationship between servant leadership ethical leadership and work engagement among support staff and to identify whether proactive personality moderate the relationship in one of Development Financial Institution (DFI) organization at Kuala Lumpur. Simple random sampling technique was used for this study where total number of 113 survey questionnaire forms was distributed to selected respondents which only 103 were usable for analysis. Preanalysis by using exploratory factor analysis found that all variables loading value was distributed consistently except for servant leadership. Post-analysis of correlation and regression analysis to test the hypotheses revealed that both ethical leadership and proactive personality has significant positive relationship towards work engagement meanwhile proactive personality negatively moderate the relationship between ethical leadership and work engagement. Based on the findings, this study provided suggestions and recommendations in terms of practical implications for organization and future academic research.